GAMBARAN HISTOPATOLOGI GINJAL TIKUS (Rattus rattus) PADA PEMBERIAN LAMTORO MERAH (Acacia villosa) ADAPTASI DAN TANPA ADAPTASI - Erda Eni Rame Hau (Politeknik Pertanian Negeri Kupang, 2016)
ABSTRACTIncubation of red acacia (Acacia villosa) leaf in preadapted rumen fluid of goat: Its effects on histopathologycal changes of kidney of rat (Rattus-rattus). This study was conducted to examine the detoxification potential of rumen microbes upon secondary compounds of Acacia villosa. Â Leaf powder of A. villosa incubated in rumen fluid of goat pre-adapted with A. villosa was fed on rats used as experimental animals. Eigthteen rats were divided into 3 groups, consisting of control, group of rats fed with A. villosa incubated in pre-adapted rumen fluid (adaptation group) and group of rats fed with A. villosa incubated in non adapted rumen fluid (non-adaptation group).That results of histopathologycal examination showed a significant higher gromerular and tubular changes in the kidneys of the non-adaptation group compared to those in the adaptation and control groups. The changes in glomerulus were edema characterized by deposition of protein in the mesangial and Bowman space, and enlargement of the Bowman space. The changes in tubules were consisting of hydropic degeneration, deposition of protein in the tubules lumen and necrosis.Key words: Acacia villosa, histopathologycal changes, adapted rumen fluid.